Electrocardiographic and echocardiographic changes in nonalcoholic fatty liver disease - Ahmed S Elsawaby; Rawia A Al-Fiky; Azza E Mohamed; Hossam El Din A Mahmoud; Shereen A Saleh; Haitham G Mohammed; Iman F Montasser; Mohammed H Abdelbary (SpringerOpen, 2019)
Context Interactions between the heart and the liver have been described. The presence and severity of nonalcoholic fatty liver disease (NAFLD) was found to be associated with increased QTc interval and subclinical cardiac abnormalities. Aim The aim of this study was to evaluate the ECG and echocardiographic changes in patients with NAFLD and their correlation with disease severity. Patients and methods This study was conducted in Ain Shams University, Ain Shams Specialized, and Helwan University Hospitals in the period from May 2015 till May 2018. It was conducted on 50 patients with NAFLD and 50 controls. Clinical, laboratory, and ultrasonographic examinations were done for all included patients together with liver biopsies. ECG and echocardiography were also performed. Independent Student's t-test, χ2-test, Fisher's exact test, and Pearson's correlation coefficient were used. Data were presented as mean±SD and number and percentage. Results Longer corrected QT was found in the NAFLD group in comparison with controls (406.6±26.8 and 380.0±24.5 ms, respectively). Significant correlation between QTc and liver size, grade of steatosis, and NAFLD activity score was found. Overall, 16 and 8% of patients with NAFLD had diastolic and valvular dysfunctions, respectively. Conclusion NAFLD is associated with significant QTc prolongation and structural heart changes, with significant correlation between QTc and disease severity.